Reliability analysis of an automated radial distribution feeder for different configurations and considering the effect of forecasted electrical vehicle charging stations - Rekha, V. Swarna; Vidyasagar, E. (Institute of Advanced Engineering and Science, 2024)
In the future, the expansion of electrical vehicles is becoming more prevalent, which requires electric vehicle charging stations (EVCS), and at the same time, distribution automation and smart grid technology will be implemented as part of the reforms in the distribution system. This paper reviews the effect of the increased EVCS, which causes an increase in the magnitude of current and moderates the average failure rate of feeder sections. The implementation of distribution automation and a smart grid reduces the average restoration time, thereby increasing the reliability of the distribution system. The number of electrical vehicles (EVs) for the years 2025 and 2030 is forecasted using Holt's model, and the corresponding average failure rate of feeder sections is calculated. The average switching time for adopting distribution automation and smart grid technology is taken as 5 seconds and 20 milliseconds, respectively. The voltages, power losses, and reliability indices are calculated assuming the EV charging points are located with equal capacity at all load buses for different configurations of radial feeders. The results are compared with the reliability indices of the feeder of all the configurations in the absence of EV charging station loads, automation, and smart grid technology. This work is validated on a standard IEEE 33 test bus system.